Free-text comments as a tool for developing the self-report method: Parents’ responses to a survey on violence against children - Ellonen, Noora (The Australian and New Zealand journal of criminology, 2018)
Self-report measures are used to study the degree of victimisation in children that have experienced violence. Very little methodological attention is, however, paid to development of these measures. In this article, we will analyse parents’ free-text comments in response to a self-report survey of their own violent behaviour towards their children. Themes presented by parents concerning violence against children as a phenomenon will be analysed and methodological input of these free-text comments in a self-report survey will be examined. Analysis is based on survey data collected in Finland in 2011 (N = 3170) including 2047 free-text comments. Based on the thematic analysis of those comments, four themes were phrased: making sense of the responses, defining violence, children and violence in society and experiencing exclusion. Parents’ comments with respect to these themes reflected the complexity of what actually constitutes violence against children. Analysis also showed that free-text comments are a valuable and ethically sound tool for developing the self-report measure.